2023
DOI: 10.3390/genes14010126
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Diagnosis of PPP2R1A-Related Neurodevelopmental Disorders Using Whole Exome Sequencing: Clinical Report and Review of Literature

Abstract: PPP2R1A-related neurodevelopmental disorder (NDD) is expressed with autosomal dominant inheritance and is typically caused by a pathogenic de novo PPP2R1A mutation. It is characterized by the predominant features of hypotonia, developmental delay, moderate-to-severe intellectual disability, agenesis of corpus callosum (ACC), ventriculomegaly, and dysmorphic features; however, none of these anomalies have been diagnosed prenatally. We report on the prenatal diagnosis of PPP2R1A-related NDD in two fetuses by who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…These patients showed different clinical manifestations such as opposite abnormal head circumference types, and microcephaly and macrocephaly. To identify the correlations between the different variations of PPP2R1A with clinical features, we collected and reviewed the clinical and genetic information of 64 NDD patients (2 reported fetuses were excluded, and 4 patients in our study were included) [ 7 , 10 , 13 , 14 , 15 , 22 ]. We found that patients with microcephaly often had brain structure abnormalities and severe epilepsy; patients with Met180Thr/Val variants displayed macrocephaly and severe ID, but did not suffer from epilepsy; patients with Arg258His/Ser variants all had microcephaly but rarely suffered from epilepsy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These patients showed different clinical manifestations such as opposite abnormal head circumference types, and microcephaly and macrocephaly. To identify the correlations between the different variations of PPP2R1A with clinical features, we collected and reviewed the clinical and genetic information of 64 NDD patients (2 reported fetuses were excluded, and 4 patients in our study were included) [ 7 , 10 , 13 , 14 , 15 , 22 ]. We found that patients with microcephaly often had brain structure abnormalities and severe epilepsy; patients with Met180Thr/Val variants displayed macrocephaly and severe ID, but did not suffer from epilepsy; patients with Arg258His/Ser variants all had microcephaly but rarely suffered from epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…Presently, diseases caused by PPP2R1A gene mutations are defined as PPP2R1A-related NDD [ 12 ], with clinical features including severe hypotonia, varying degrees of intellectual impairment and developmental delay, abnormal head circumference, epilepsy, attention deficit, dysplasia of the corpus callosum, etc. Currently, more than 60 patients have been reported [ 2 , 4 , 7 , 10 , 13 , 14 , 15 ]. These variations may change the subunit-binding feature or affect holoenzyme activity [ 7 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…All previously reported pathogenic variants in PPP2R1A (seventeen to date) are clustered close to the regulatory subunit-binding region of the protein, accumulating in HEATs 4–7 [ 1 , 4 , 5 , 6 , 7 , 8 , 9 ] ( Figure 2 , Supplementary Table S1 ) and causing single-amino-acid substitution. These variants generate a dominant negative effect and there is compelling evidence that the severity of the phenotypic spectrum correlates with biochemical dysfunctions [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…The PPP2R1A protein is composed of 15 HEAT (huntingtin, elongation factor 3, protein phosphatase 2A, and yeast kinase TOR1) repeat motifs, of which HEATs 1–8 mediate interactions with a specific regulatory B subunit [ 4 ]. Among the 46 patients reported to date, forty-five showed pathogenic variants that accumulate in HEATs 4–7 [ 1 , 5 , 6 , 7 , 8 , 9 , 10 ], generating a dominant negative effect, and causing biochemical dysfunction in the majority of them [ 1 , 7 ]. The subjects reported with PPP2R1A -related neurodevelopmental disorder (NDD) show a consistent neurological phenotype (corpus callosum hypoplasia, epilepsy, moderate-to-severe intellectual disability, and ventriculomegaly) but the clinical spectrum is expanding and extraneurological features, such as congenital heart disease, have recently been reported [ 8 ].…”
Section: Introductionmentioning
confidence: 99%